In Situ Salivary Multi-Ion Determination Chip Based on an Organic Electrochemical Transistor with EG-Modified PEDOT:PSS - Jang, Yamujin; Choi, June-Heang; Lee, Soo-Hyun; Lee, Yi-Jae (AMER CHEMICAL SOC, 2025)
In this study, the multi-ion detection chip (MIDC) with an ethylene glycol-modified PEDOT:PSS (EGPP)-based organic electrochemical transistor (OECT) was designed, fabricated, and characterized for in situ salivary ion determination applications. As the channel material for the OECT, EGPP was selectively coated onto the patterned drain and source electrodes. The fabrication sequence was performed using a semiconductor batch process. With wafer-scale processing, the fabricated unit MIDC (10 × 10 mm2) with EGPP-based OECT coated with ion selective membrane (ISM) as sensing layers measures the concentration of K+, Na+, Ca2+, and Cl？ concentration range lower than 10？5 M to a resolution of ∼2 × 10？3 log concentration range. These ions were selected because of their prominence in body metabolism. We used the 4-different channel for selective multi-ion determination, and an additional 1-channel array was used for salivary glucose determination. Because all of the sensing layers simultaneously measured the same analyte solution, we investigated its resistance to interference among the analytes. Additionally, we evaluated its practical feasibility from the response of multi-ions in an artificial saliva sample. The performance of this chip platform is suitable for applications such as personalized in situ healthcare and water quality monitoring.